Himno Patriótico de Alejandro Cardona y Llorens (1827-1899) - Vargas Cullell, María Clara (2022)
This article studies the various facets of the musical profession of Alejandro Cardona y Llorens, a Spanish migrant musician who settled in Costa Rica from 1853. The musical activities that he undertook throughout his life reflect the process of professionalization of the musical profession that began in the country from the second half of the 19th century. It ́s also an example of how migration has been an element that has contributed to the diversification and consolidation of the country’s musical practice at various times in history.